Cemeteries and the Life of a Smoky Mountain Community Cades Cove Under Foot - Foster, Gary S.; Lovekamp, William E. (Springer International Publishing : Imprint: Palgrave Pivot, 2019)
Foster and Lovekamp offer a clear approach to reconsidering our cemeteries as a valued source of data and community history. In placing Cades Cove cemeteries into the context of spatial and social trends of their era, the authors help us understand life and death for people living in the Great Smoky Mountains before its designation as a national park. -James Maples, Associate Professor of Sociology, Eastern Kentucky University, USA In one of the few studies to draw upon cemetery data to reconstruct the social organization, social change, and community composition of a specific area, this volume contributes to the growing body of sociohistorical examinations of Appalachia. The authors herein reconstruct the Cades Cove community in the Great Smoky Mountains of Tennessee, USA, a mountain community from circa 1818 to 1939, whose demise can be traced to the establishment of the Great Smoky Mountains National Park. By supplementing a statistical analysis of Cades Cove's twenty-seven cemeteries, completed as a National Park Study (#GRSM-01120), with ethnographic examination, the authors reconstruct the community in detail to reveal previously overlooked social patterns and interactions, including insight into the death culture and death-lore of the Upland South. This work establishes cemeteries as window into (proxies of) communities, demonstrating the relevance of socio-demographic data presented by statistical and other analyses of gravestones for Appalachian Studies, Regional Studies, Cemetery Studies, and Sociology and Anthropology.